Choices In Life Reflected In Angela Morrison's Sing Me To Sleep Novel (2010): An Existentialist Criticism - Yantiningsih, Tri; , Dr. Muhammad Thoyibi, M. S.; , Mauly Halwat Hikmat, Ph. D. (2013)
The major issue in this study is how people make the choices in life is reflected in Angela Morrison's Sing Me to Sleep novel (2010): An existentialist criticism. The objective of this study is to analyze Sing Me to Sleep novel based on existentialist criticism. There are two types of data source in this method; they are primary and secondary data source. The primary data source is the novel and the secondary data is documentation and other material related to the study. Both data are collected through library research. The technique used in analyzing the data is descriptive analysis. The result of the study shows that in the novel Morrison illustrates an existential situation in which an individual is trying hard to make her life meaningful by making existential choices. Angela Morrison also suggests that what is good to an individual should also be good to others.